A A Review of Budding and Grafting Techniques in Horticultural Crops: Efficiency and Determining Factors: Tinjauan Teknik Okulasi dan Sambung pada Tanaman Hortikultura: Efisiensi dan Faktor Penentu - Rafila, Zacki; Violita, Violita (Microbiotech, 2026)
Budding and grafting are among the most widely applied artificial vegetative propagation techniques in horticultural crops due to their ability to improve propagation efficiency, preserve desirable traits from parent plants, and accelerate fruit production. This review aims to examine various budding and grafting techniques applied to horticultural commodities such as durian (Durio zibethinus), citrus (Citrus spp.), avocado (Persea americana), cacao (Theobroma cacao), rambutan (Nephelium lappaceum), mango (Mangifera indica), and langsat (Lansiumdomesticum). A descriptive-analytical literature review method was employed, focusing on peer-reviewed scientific articles published between 2015 and 2025. The findings indicate that the success of vegetative propagation is significantly influenced by the type of technique used, physiological compatibility between scion and rootstock, and environmental factors such as humidity and temperature. Techniques such as top cleft grafting, wedge grafting, and chip budding have shown high success rates in specific crops. However, propagation failures are also reported, especially when there is a lack of taxonomic proximity between graft partners. Therefore, the selection of appropriate propagation techniques, combined with proper environmental management and compatible plant material, is crucial to enhancing the success rate of vegetative propagation in horticultural crops.